Las infecciones de vías urinarias mediante uroanalisis y sus consecuencias en parto prematuro en embarazadas en Barreiro nuevo cantón Babahoyo provincia de Los Ríos de abril a octubre del 2014. - Carabedo España, Deandra Anais (2014)
El abstract problem, threat of premature birth is a leading cause of perinatal morbidity-mortality caused by urinary tract infection in our country, attending the Canton Babahoyo province of rivers, here came the present research work. The objectives of the research were to determine the Etiologic Agent in urinary tract, inducing the threat of preterm birth since the infection of urinary tract in pregnancy is a complication of greater danger in the pregnant women, the methodology used for this research is based on the descriptive study of patients with this disease in the period between April of 2014 to October 2014 which found a universe of 100 patients who represent problems of urinary tract infection of which most present a clinical picture compatible with the disease more threat of preterm birth which samples it is 50 patients who had urinary tract infection problems both the collection held in the institution. For collecting the sample survey was applied as an instrument of investigation the structured with closed and open questions. the results were, by the chemical examination and sediment through the microscope was observed large number of bacteria, leukocytes, epithelial cells and red blood cells which can say that there is a urinary tract infection for which the gynaecologist responsible for control of the pregnancy will prescribe medications or other examination of urine ¨urocultivo¨, for this reason we consider that the consultation of a pregnant woman should always focus to early diagnosis, treatment, prevention, and information to the expectant mother risks and general recommendations that should be against this entity.